Human Well-being and In-Work Benefits: A Randomized Controlled Trial - Richard Dorsett; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2014)
Many politicians believe they can intervene in the economy to improve people's lives. But can they? In a social experiment carried out in the United Kingdom, extensive in-work support was randomly assigned among 16,000 disadvantaged people. We follow a sub-sample of 3,500 single parents for 5 ensuing years. The results reveal a remarkable, and troubling, finding. Long after eligibility had ceased, the treated individuals had substantially lower psychological well-being, worried more about money, and were increasingly prone to debt. Thus helping people apparently hurt them. We discuss a behavioral framework consistent with our findings and reflect on implications for policy.
Keywords: I31; D03; D60; H11; J38; 330; randomized controlled trials; government policy; in-work benefits; wage subsidies; well-being; happiness